L'appropriation collective d'un dispositif pédagogique à l'école primaire. La construction d'un compromis provisoire entre des principes de justice différents : le cas du « plan de travail » - Gwénaël Lefeuvre; Bruno Fondeville; Rémi Bonasio; Philippe Veyrunes (Nantes Université, 2019)
As part of a research conducted in support of a primary school, we will question the collective ownership process of a particular educational device designed by the teaching team: the work plan. The objectives of teachers from this device, are to promote the individualisation of academic learning of students, taking into account their individual rhythms and promote their autonomy in work. Using data from group meetings conducted within research and support, we will analyze the reasons that teachers mobilize to build agreements for the device used. The sociology of justification (Boltanski and Thevenot, 1991) will be convened to highlight the tradeoffs that characterize the device from particular value systems and different "worlds" from which refer teachers to coordinate their actions within the device